What are the management recommendations for deer tick exposure?. Issue 4 (April 2017) - Saygan, Kristine; Juan, Maria San
Abstract : EVIDENCE‐BASED ANSWER : Single‐dose doxycycline in a Lyme hyperendemic area decreases the incidence of erythema migrans in high‐risk patients by 2.8% if given within 72 hours after an Ixodes scapularis tick bite (SOR: B, single RCT). Amoxicillin does not decrease the incidence of erythema migrans following an I scapularis tick bite (SOR: B, single RCT). Patients who develop possible symptoms of Lyme disease after tick removal should seek medical attention (SOR: B, evidence‐based guideline).